Children First, Offenders Second Positive Promotion: Reframing the Prevention Debate. (December 2015) - Case, Stephen; Haines, Kevin
This article explores the concept of 'prevention' in youth justice, which is dominated by negative, retrospective, risk-focused, offender-first approaches that individualise the causes of offending by children and responsibilise children for failing to resist and negotiate these causes. We offer an alternative 'prevention' model that prioritises the promotion of positive behaviours and outcomes for children. Children First, Offenders Second positive promotion is grounded in child-friendly principles of universalism, diversion and normalisation, progressed through inclusionary, participatory and legitimate practice and evidenced through measurable behaviours and outcomes such as engagement with youth justice processes and access to universal entitlements.